Nurse's quick check : fluids & electrolytes. (LWW medical book collection., 2005)
Designed for quick reference in the hospital hallway or at the nurses' station, this handbook presents succinct, bulleted, up-to-the-minute information on fluid and electrolyte homeostasis and common fluid, electrolyte, and acid-base imbalances. Part 1 provides a rapid refresher on key facts nurses need to evaluate assessment findings related to fluid and electrolyte homeostasis. Part 2 contains entries on imbalances, which are are alphabetically organized and presented on easy-to-scan two-page spreads. Numerous tables and illustrations are included. Logos highlight potentially dangerous situa.